Pengaruh Electronic Word of Mouth Credibility (e-WOM Credibility), Kepercayaan Konsumen, dan Gaya Hidup Terhadap Loyalitas Pelanggan pada Pembelian Produk Wardah - Dwi Putri Utami; Mukhroji Mukhroji (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The present study aims to examine the effect of e-WOM credibility, consumer trust, and lifestyle on customer loyalty toward Wardah products. Data were obtained through questionnaires distributed to consumers who had purchased and used Wardah products, and subsequently analyzed using multiple linear regression analysis. The partial test results indicate that all three variables exert a positive yet not statistically significant effect on customer loyalty. Nevertheless, when tested simultaneously, the effect was found to be significant. The R² value of 21.9% indicates that the proposed model accounts for approximately one-fifth of the variation observed in customer loyalty. These findings suggest that customer loyalty is not shaped by a single determining factor, but rather emerges from the combined influence of multiple variables. The credibility of digital information, brand trust, and the alignment between the product and consumers' lifestyles collectively contribute to shaping repurchase behavior toward Wardah products. Keywords: e-WOM credibilit; consumer trust; lifestyle; consumer loyalty.